Chemical composition and biological activity of essential oil of Teucrium scordium L. subsp. scordioides (Schreb.) Arcang. (Lamiaceae) from Sardinia Island (Italy). Issue 22 (17th November 2022) - Piras, Alessandra; Maccioni, Alfredo; Falconieri, Danilo; Porcedda, Silvia; Gonçalves, Maria José; Alves-Silva, Jorge M.; Silva, Ana; Cruz, Maria Teresa; Salgueiro, Ligia; Maxia, Andrea
Abstract: The aim of this study is to demonstrate the antifungal, anti-inflammatory and anti-migratory potential of the essential oil of Teucrium scordium subsp. scordioides (Schreb.) Arcang, a plant widely used in traditional medicine in Sardinia. The oil was rich in germacrene D (25.1%), δ-cadinene (12.9%) and alloaromadendrene (11.3%). The yeast Cryptococcus neoformans and the dermatophytes Trichophyton rubrum, T. mentagrophytes var. interdigitale and Epidermophyton floccosum were the most susceptible fungi to the action of the oil. In lipopolysaccharide (LPS)-stimulated macrophages, the oil was able to decrease nitric oxide production by ca. 30% at 1.25 μL/mL, without affecting cell viability. In the scratch wound assay, it allowed for ca. 36% of wound closure after 18 h, thus showing anti-migratory properties. Overall, this study highlights the potential of this species to mitigate fungal infections associated with an inflammatory response. Furthermore, we also reported for the first time its anti-migratory capacity, thus suggesting anticancer properties. Graphical Abstract: UF0001